2020
DOI: 10.1007/s10973-020-09365-9
|View full text |Cite|
|
Sign up to set email alerts
|

Review on the recent progress in the preparation and stability of graphene-based nanofluids

Abstract: Graphene has attracted much attention from the science world because of its mechanical, thermal, and physical properties. Graphene nanofluid is well known for its easy synthesis, longer suspension stability, higher heat conductivity, lower erosion, corrosion, larger surface area/volume ratio, and lower demand for pumping power. This article is an audit of experimental outcome about the preparation and stability of graphene-based nanofluids. Numerous researches to prepare and stabilize graphene-based nanofluids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 231 publications
(254 reference statements)
1
42
0
Order By: Relevance
“…Relative viscosity is obtained by dividing the viscosity of nanofluids by that of the base fluids. It can be seen that the viscosity is higher with nanoparticle content due to the clusters formed from nanoparticles [6]. Temperature plays an essential role in the relative viscosity.…”
Section: Rheological Properties Of Halloysite Nanofluidmentioning
confidence: 99%
See 3 more Smart Citations
“…Relative viscosity is obtained by dividing the viscosity of nanofluids by that of the base fluids. It can be seen that the viscosity is higher with nanoparticle content due to the clusters formed from nanoparticles [6]. Temperature plays an essential role in the relative viscosity.…”
Section: Rheological Properties Of Halloysite Nanofluidmentioning
confidence: 99%
“…By visual observation, it can be confirmed that the SCMC is the best choice. Colloidal solutions with zeta potentials as low as -30 mV have acceptable stability [6,58]. Table 4 shows the zeta potential values of HNT nanofluids with different concentrations.…”
Section: Zeta Potential Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the role of GO in featured rheology was analyzed such as an examination of GO-SiO 2 nanoparticles for unconventional reservoir shales to reduce cutting dispersion [ 128 ], suspension of cutting fluids using GO [ 133 ], improved thermal stability and inhibition capabilities of WBDF in Woodford shale [ 134 ], the effect of GO functionalization to improve heavy oil recovery [ 135 ], clean swelling inhibitor in WBDF [ 97 ], and GO as an additive to improve filtration, thermal conductivity, and rheological properties of drilling fluids [ 116 , 136 ].…”
Section: Graphene Impacts In Drilling Operationsmentioning
confidence: 99%